RETRACTED: The influence of complex genotypes in the PRL and β-LG genes in Lacon sheep breed on cheese producing - Selionova M.I.; Gladkikh M.Yu.; Evlagina D.D.; Glushenko M.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001